Narasi Religiusitas Politik : Strategi Calon Gubernur Kalimantan Selatan Pada Pemilukada 2020 - Wahdini, Muhammad (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
South Kalimantan, which is dominated by the Banjar tribe, has a strong religious culture in various sectors, including the political sector. Tuan Guru's role is very important in the political map of South Kalimantan, so that in every political contest, Tuan Guru's role cannot be ignored in gaining public support for candidates. As the one-election governor of 2020, the role of Tuan Guru is very influential in the process of winning one of the candidate pairs. This paper aims to analyze the pattern of religious narratives in politics that occur in Indonesia's Borneo South. In addition, this paper also analyzes the role of Tuan Guru in the world of politics in South Kalimantan. This writing was produced from a literature review with data sources in the form of important research results related to religious and political issues in Kalimantan. This paper also uses articles that are directly related to the issue at hand. This paper argues that the narrative of political religiosity is a strategy used by candidate pairs to gain the sympathy of voters. The approach with Tuan Guru carried out by the candidates was, in fact, very effective in gaining votes in the gubernatorial election process.